Pengaruh Agama Kristen Terhadap Konsep Kehidupan Setelah Kematian dalam Budaya Batak Toba - H. Anak Ampun, Hastuti; Pangga, Yakobus (STP St. Bonaventura Medan, 2023)
Before evangelization by the Catholic Church reached Batak land, the Batak people themselves already had the concept of belief in the supreme being, namely Mulajadi Na Bolon. This belief is known as parmalim. In this concept not only talks about the system of life, but also touches on creation and even life after death. The concept of life after death in traditional Batak religion is very different from the concept of life after death in Catholicism. The purpose of this research is to see the influence of Catholicism on the concept of life after death in Batak culture. This research uses the literature research method. The results show that the Batak ancestor worship ceremony is based on the Batak traditional religion's concept of life after death, that ancestral spirits are able to influence the lives of the living, able to give blessings or curses. The presence of Christianity purified this concept, that the ceremony to the ancestors is a form of respect and compassion for those who have died, which is intended to pray for the salvation of their souls.